Physiological and neuromuscular response to a simulated sprint-distance triathlon: effect of age differences and ability level - Garcia-Pinillos, F.; Cámara-Pérez, J. C.; González-Fernández, F. T.; Párraga-Montilla, J. A.; Muñoz-Jiménez, M.; Latorre-Román, P. Á. (The Journal of Strength and Conditioning Research, 2016)
This study aimed to describe the acute impact of a simulated sprint-distance triathlon at physiological and neuromuscular levels and to determine whether age and athletic performance influenced the response in triathletes. Nineteen triathletes performed a sprint-distance triathlon under simulated conditions. Cardiovascular response was monitored during the race. Rate of perceived exertion along with muscular performance parameters (countermovement jump [CMJ], squat jump [SJ], and handgrip strength test [HS]) were tested at pre- and posttest and during every transition, while a 20-m sprint test (S20m) was performed before and after the race. Blood lactate was recorded postrace. A repeated measures analysis of variance showed that the neuromuscular response—in terms of CMJ, SJ, and HS—was unchanged (p = 0.05), while S20m performance was impaired at posttest (p < 0.001). A linear regression analysis showed that dCMJ predicted the overall race time (R2 = 0.226; p = 0.046). In addition, 2 cluster analyses (k-means) were performed by grouping according to athletic performance and age. Between-group comparison showed no significant differences in the impact of the race at either the physiological or the neuromuscular level. The results showed that muscular performance parameters were not impaired throughout the race despite high levels of fatigue reported. However, despite maintaining initial levels of muscle force after the race, the fatigue-induced changes in S20m were significant, which could reinforce the need to train sprint ability in endurance athletes. Finally, despite the differences in ability level or in age, the acute physiological and neuromuscular responses to a simulated sprint-distance triathlon were similar.